VALIDITAS MEDIA PEMBELAJARAN ANIMASI TATA SURYA DALAM PEMBELAJARAN STUDENT TEAM ACHIEVEMENT DIVISION (STAD) - Muhammad Wildan Ainun Sholeh; Erman Erman; Wahyu Budi Sabtiawan (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2020)
This study aims to describe the validity of the solar system animation learning media used in STAD learning. The subject of this research is the animation media that includes material for the junior high school solar system. The validity of the animation media is determined based on the validation results sheet which is assessed by experts. Analysis of the results of the validation was carried out using a quantitative descriptive method by giving an assessment by experts who were then known to score mode and media criteria. Animation media has several aspects to be assessed, namely general aspects, material aspects, audio-visual aspects, and technical aspects. The assessment from the experts shows that the validation sheet of the solar system animation media in STAD learning has a score of 4 which shows very valid criteria. This shows that the Solar System animation media is appropriate to be used in STAD learning at the junior high school level.